2022
DOI: 10.2166/wcc.2022.121
|View full text |Cite
|
Sign up to set email alerts
|

Response of runoff and nitrogen loadings to climate and land use changes in the middle Fenhe River basin in Northern China

Abstract: Investigating and understanding the responses of runoff and nitrogen loading to climate and land use change is particularly important for future water resources management. In this article, the Soil and Water Assessment Tool (SWAT) was used to simulate runoff and nitrogen loading in the middle reaches of the Fenhe River. The model was calibrated by the SWAT calibration and uncertainty procedure (SWAT-CUP) to achieve the accuracy of simulating runoff and nitrogen loadings. Furthermore, 20 climate change scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…According to Harrison et al, in the mid-1990s, global reservoirs eliminated 464 Gmol N annually (Harrison et al, 2009;Harrison et al, 2010;Van Cappellen and Maavara, 2016). Denitrification, the major nitrogen removal mechanism in reservoirs, contributes to approximately 58-59% of the total removal (Zhu et al, 2022).…”
Section: Variations In Hydraulic Conditionsmentioning
confidence: 99%
“…According to Harrison et al, in the mid-1990s, global reservoirs eliminated 464 Gmol N annually (Harrison et al, 2009;Harrison et al, 2010;Van Cappellen and Maavara, 2016). Denitrification, the major nitrogen removal mechanism in reservoirs, contributes to approximately 58-59% of the total removal (Zhu et al, 2022).…”
Section: Variations In Hydraulic Conditionsmentioning
confidence: 99%
“…Agricultural land generally produces the largest N load, followed by tea plantations, citrus groves and woodlands (Zhang, Li, et al., 2020). Although urban land accounts for a small proportion in agricultural watersheds, it increases the proportion of impervious surface, reduces land permeability, leads to higher runoff amount and non‐point source N load especially during rainy seasons (Alamdari et al., 2022; Vystavna et al., 2023; Zhu et al., 2022). N fertilization can increase crop yield, but cannot be fully absorbed by crops, and then partially enter rivers and lakes through runoff or seepage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that climate change is influencing the water cycle, leading to shifts in low, mean, and high streamflow (Gudmundsson et al, 2021). These changes in temperature and precipitation have long-term effects on water resources, with climate change intensifying in the coming decades (Zhu et al, 2022). The global mean surface temperature is estimated to have increased by 0.74°C ± 0.18°C from 1906 to 2005, nearly twice as much warming in the past 50 years as in the past 100 years (Trenberth et al, 2007).…”
Section: Introductionmentioning
confidence: 99%